A Socio‐Spatial Combined Approach Confirms a Highly Compartmentalised Structure in Honeybees. (11th August 2014) - Baracchi, David; Cini, Alessandro; Fusani, L.
Abstract Complex insect societies are formed by thousands to millions of individuals which incessantly interact in the sheltered nest space under the constant pressure of different challenges, such as infectious disease and group coordination. Understanding how colony members interact in space and time may therefore help unravelling how different evolutionary pressures have moulded insect societies. We investigated the spatial positions and the association network of workers and the queen in the honeybee (Apis mellifera) society using high‐resolution recordings of spatial behaviour and 'network connections' at the individual level. Our socio‐spatial combined approach highlighted a highly compartmentalised structure inside honeybee colony. Connectivity and spatial overlap are high among same‐age workers but low among different‐age workers. Foragers are at the periphery of the social network, while the colony core is formed by young bees and the queen. Our study presents the first empirical quantitative description of socio‐spatial organisation of a honeybee hive, confirming a highly compartmentalised structure and highlighting how the pressures exerted by ergonomics requirements could have shaped insect societies.